Financial Performance Evaluation for PT XYZ’s Subcontractor Selection for PIT X Mining Project at PT VWX - Rico Wanardijaya; Erman Arif Sumirat; Sylviana Maya Damayanti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study is conducted to support PT XYZ in identifying the most financially sound subcontractor for executing the PIT X mining project, commissioned by PT VWX. Given PT XYZ’s limited working capital, the company plans to delegate the project to one of several publicly listed subcontractors. To make an informed decision, a comprehensive assessment of financial performance is essential to ensure the selected firm can handle both the operational and financial demands of the project.The research utilizes financial ratio analysis focused on four primary dimensions: liquidity, activity, solvency, and profitability. Key indicators such as the current ratio, quick ratio, total asset turnover, debt ratio, interest coverage, net profit margin, return on assets, and return on equity are applied to evaluate three shortlisted subcontractors: PT Darma Henwa Tbk (DEWA), PT Delta Dunia Makmur Tbk (DOID), and PT Petrosea Tbk (PTRO). The Weighted Scoring Method (WSM) is used to assign importance to each ratio based on strategic value, resulting in a composite score that reflects each company’s overall financial condition.The findings indicate that PT Petrosea (PTRO) secures the highest weighted score, suggesting it possesses superior financial stability and operational effectiveness compared to the others. PTRO shows consistent strength in asset management, solvency, and profitability, making it the top candidate for subcontracting the PIT X project. This study presents a structured, evidence-based model for evaluating subcontractors, which can be extended to vendor selection practices in other capital-intensive sectors.